SURGICAL TACTICS IN PATIENTS WITH MULTILOCULAR POST-TRAUMATIC RETROPERITONEAL CYST - B. V. Sigua; V. P. Zemlyanoy; A. A. Kozobin; D. F. Сherepanov; A. V. Danshov; V. V. Shustov (Неотложная медицинская помощь, 2017)
Treatment of patients with complicated course of post-traumatic retroperitoneal cysts is a difficult task due to the relative rarity of this disease. The absence of a single treatment and diagnostic algorithm for this group of patients contributes to the high mortality rate. This clinical case demonstrates the complexities of diagnosis and surgical treatment of patients with multilocular post-traumatic retroperitoneal cyst complicated by recurrent bleeding into the cavity of the cyst and violation of the blood supply to the right side of the colon.